Factors Affecting Adoption of a Quantitative Method for R&D Project Selection - Maher, P. Michael; Rubenstein, Albert H. (Management Science, 1974)
In the field of research and development (R&D), “state-of-the-art” project selection models are not being widely adopted. This paper reports on the results of an attempt to develop, test, and evaluate systematically an R&D project selection technique in an operating R&D organization. The technique employed was a modified risk analysis model. The results suggest that an individual's assessment of the value of the data generated by an R&D project selection technique is an extremely important factor in determining his willingness to adopt the technique. The relative importance of two determinants of adoption: perceived changes in organizational processes resulting from the use of a project selection model and the importance of the strategies used to introduce a model into an organization, appear to run counter to the thinking of many management theorists who tend to emphasize the importance of the organizational process and the importance of the strategy for change.